The special education program in the city schools, manila: an appraisal - Layco, Erlinda A. (Manila : National University, 1998)
This study revolved around the evaluation of the Special Education Program of the City Schools of Manila in terms of the internal efficiency of its social, cultural and economic subsystem, during the school year 1997-1998 as gleaned and suggested by the perception-evaluation of the SPED teachers themselves.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.